Family perception of humane care provided by health care personnel - Luz Marina Bautista Rodriguez; Yari Paola García Calderón; Lessly Johana Medina Chaves; Karley Ginary Cruz Hernández (Universidad Francisco de Paula Santander, 2018)
Objective: To determine the perception the family has about the humane care in the Intensive Care Units of three Health Service Institutions in the city of Cucuta (Colombia). Materials and Methods: A quantitative cross-sectional descriptive study was performed with a sample of 220 family members that met the requirements of inclusion; for the recollection of the information, the instrument used was denominated Family perception about humanization in the intensive care units, designed and validated in Cucuta by students and teachers of VIII semester from the Nursing Program at the University Francisco de Paula Santander in 2016. To determine the liability the Cronbach's Alpha was used, obtaining a value of 0.89. Results: The humane care perception by family members was moderate in 63% of the participants. The communication and information, emotional support and family participation were the highest rating categories, while coping and visits had the lowest ratings. Conclusions: The participants of the study perceive as moderate the humane care, since they relate this to the quality of the care provided, considering the evaluated categories in the research. On the other hand, the family members point out that they receive the necessary information and support to involve themselves in the care activities, allowing them for more interaction with the hospitalized familiar and the personnel.